Super-Refractory Status Epilepticus Treated with High Dose Perampanel: Case Series and Review of the Literature - Christopher R. Newey; Naresh Mullaguri; Stephen Hantus; Vineet Punia; Pravin George (Case Reports in Critical Care)
Introduction. Acute symptomatic seizures are frequent in the critically ill patient and can be difficult to treat. The novel anticonvulsant perampanel may be effective in the treatment of status epilepticus considering its mechanism of action of being an AMPA antagonist. We present four cases of super refractory status epilepticus treated with high dose perampanel. Method. Case report. Cases. Four patients were treated with perampanel for their refractory status epilepticus. One patient had new onset refractory status epilepticus of unknown etiology. Three other patients had status epilepticus as a result of their cardiac arrest. Two of the cardiac arrest patients had myoclonus. In all patients, the additional of perampanel resulted in a reduction of seizure burden without affecting hemodynamics or hepatic or renal function. Conclusion. Perampanel may be effective in the treatment of super-refractory status epilepticus of varying etiologies. A larger, prospective study is needed to further assess this therapy.